Time Is Money: The Decision Making of Smartphone High Users in Gain and Loss Intertemporal Choice - Tang, Zixuan; Zhang, Huijun; Yan, An; Qu, Chen (Frontiers in Psychology, 2017)
Nowadays the smartphone plays an important role in our lives. While it brings us convenience and efficiency, its overuse can cause problems. Although a great number of studies have demonstrated that people affected by substance abuse, pathological gambling and internet addiction disorder have lower self-control than average, scarcely any study has investigated the decision making of smartphone high users by using a behavioral paradigm. The present study employed an intertemporal task, the Smartphone Addiction Inventory (SPAI) and the Barratt Impulsiveness Scale 11th version (BIS-11) to explore the decision control of smartphone high users in a sample of 125 college students. Participants were divided into three groups according to their SPAI scores. The upper third (69 or higher), middle third (from 61 to 68) and lower third (60 or lower) of scores were defined as high smartphone users, medium users and low users respectively. We compared the percentage of small immediate reward/penalty choices in different conditions between the three groups. Relative to the low users group, high users and medium users were more inclined to request an immediate monetary reward. Moreover, for the two dimensions of time and money in intertemporal choice, high users and medium users showed a bias in intertemporal choice task among most of the time points and value magnitude compared to low users. These findings demonstrated that smartphone overuse was associated with problematic decision-making, a pattern similar to that seen in persons affected by a variety of addictions.